The Association Between the Presence of Human Facial Mites Demodex (Acari, Demodicidae) and Dermatological Symptoms in Rosacea Patients in Central Anatolia, Türkiye - Kahraman, Merve; Akın Polat, Zübeyda; Esen, Mustafa; Çoban Gül, Feride (Galenos Publishing House, 2024)
Objective: This study aimed to investigate the potential relationship between the presence of Demodex mites and dermatological symptoms in patients with rosacea in the Central Anatolian Region of Türkiye. Methods: A total of 63 patients diagnosed with rosacea were enrolled in the study. Skin samples were obtained using a standardized skin surface biopsy technique, and a questionnaire was administered to assess skin symptoms. Statistical analysis was performed to evaluate the association between Demodex infestation and specific skin symptoms. Results: Among the study participants, 65.1% exhibited Demodex infestation. Statistical analysis revealed significant associations between the presence of Demodex and skin burning (p=0.018), skin pain (p=0.012), and skin stinging (p=0.001). However, no statistically significant associations were observed between Demodex presence and gender, skin dryness, itching, irritation, skin rash or the presence of red/pink bumps on the skin. Conclusion: This study provides evidence suggesting a potential role for Demodex mites in the pathogenesis of rosacea, specifically in relation to skin symptoms such as burning, pain, and stinging. The findings underscore the complexity of the relationship between Demodex infestation and rosacea and highlight the need for further research, including longitudinal and mechanistic studies, to better understand this association and its clinical implications. Ultimately, understanding the role of Demodex mites in rosacea may lead to innovative therapeutic approaches, offering hope for improved management of this challenging dermatological condition. © 2024 Turkish Society for Parasitology.
Türkiye’nin Orta Anadolu Bölgesi’ndeki Rosacea Hastalarında İnsan Yüz Akarları Demodex (Acari, Demodicidae) Varlığı ile Dermatolojik Semptomlar Arasındaki İlişki
Keywords: Demodex; dermatological symptoms; rosacea